MILTEFOSINE LOADED MESOPOROUS ZINC OXIDE NANOPARTICLES TO ENHANCE ORAL BIOAVAILABILITY AND SAFETY PROFILE: A PRETOXICOLOGICAL AND PHARMACOKINETIC STUDY - GHOSH, PARAG; DINDA, SUBAS CHANDRA; DEWAN, DEBAJIT; ROY, SUKANTA; DAS, DIBYA; DAS, SOURAV; BOSE, ANIRBANDEEP (International Journal of Applied Pharmaceutics, 2025)
Objective: Miltefosine, the only approved oral therapy for leishmaniasis, is clinically limited by its poor bioavailability and significant gastrointestinal and systemic toxicities. This study aimed to develop and evaluate a novel oral formulation of miltefosine encapsulated in mesoporous zinc oxide nanoparticles (MF-ZnO NPs) to enhance its pharmacokinetic Safety Profile. Methods: MF-ZnO NPs were synthesized via a templated method, achieving a particle size of 178 nm and a drug loading efficiency of 60%. Stability studies were conducted in simulated gastric and intestinal fluids to assess nanoparticle integrity. In vitro drug release was evaluated in PBS (pH 6.8), showing a biphasic pattern with sustained release. A 28 d subacute oral toxicity study was performed in wistar rats across escalating dose groups, with raw miltefosine as a comparator. Parameters assessed included behavioral toxicity, biochemical markers (ALT, AST, creatinine, urea, bilirubin), organ weights, and histopathological scoring. Pharmacokinetic studies in rats determined systemic exposure and bioavailability enhancements. In vivo skin deposition was also assessed after 24 h. Results: MF-ZnO NPs demonstrated excellent physicochemical stability and controlled biphasic drug release with 95% cumulative release at 72 h. Toxicological evaluation revealed minimal hepatic and renal toxicity at low and medium doses, whereas high-dose MF-ZnO NPs and raw miltefosine induced significant organ damage. Pharmacokinetic analysis showed improved oral bioavailability (AUC₀–inf: 7375.9±609.56 vs. 5539.7±240.99 h·µg/ml) and prolonged half-life (73.84±11.32 h vs. 57.29±5.61 h) for MF-ZnO NPs. Skin deposition studies confirmed a fourfold increase in localized drug accumulation with the nanoparticle formulation. Conclusion: Encapsulation of miltefosine in mesoporous ZnO nanoparticles significantly enhanced its oral bioavailability, reduced systemic toxicity, and improved dermal deposition. MF-ZnO NPs present a promising oral delivery strategy for safer and more effective miltefosine therapy.